The metaphysics of Dante's Comedy - Moevs, Christian (Reflection and theory in the study of religion., 2005)
Moevs offers a treatment of the metaphysical picture that grounds and motivates 'The Divine Comedy', and the relation between those metaphysics and Dante's poetics. He arrives at the conclusion that Dante believed that all of what we perceive as reality is in fact a creation or projection of conscious being.